Afghanistan Development Update, April 2016 - World Bank (World Bank, Washington, DC, 2016)
The withdrawal of international security forces since 2014 and continuing political uncertainties have resulted in a significant deceleration to economic growth, with fiscal pressures increasing as security threats mount. However, to a significant extent, Afghanistan has successfully managed the immediate challenges resulting from the transition. It has maintained macroeconomic stability and established the conditions for a slow recovery of the economy. Risks to the economy remain significant, and it is vital that the Government identify new sources of growth to replace the declining donor inflows over the longer-term. The medium-term outlook points towards a slow recovery over the next three years. The rate of growth is projected to reach 1.9 percent in 2016, assuming adjustments in firms and households’ behavior in the context of the deteriorating security environment. Growth is projected to gradually increase from 1.9 percent in 2016 to 3.6 percent in 2018, if the political situation stabilizes and planned reforms are successfully implemented. On the other hand, any deterioration in the security environment could weaken growth prospects, with this risk being the most significant faced by the country.